Attitude towards tele rehabilitation-based therapy services and its associated factors among health professional working in specialized teaching hospitals in Amhara region, Northwest Ethiopia. (2023) - Sidelil, Habile; Demissie, Adina; Demissie, Getu Debalkie; Fikade, Berhanu; Hailegebreal, Samuel; Tilahun, Binyam
Abstract: Background: Tele-rehabilitation is part of Tele-health (TH) which provides a rehabilitation service at a distance through using telecommunication technology. The lack of skilled staff, accessibility concerns, high transportation costs, lengthy waiting times, and mobility issues make face-to-face rehabilitation treatment difficult. Therefore, this study aimed to assess attitudes and its associated factors of health professionals towards TR services. Method: An institutional-based cross-sectional study design was conducted among 408 health professionals from March to April 2021. A simple random sampling technique was applied to select study participants. Epi-data 3.1 versions software was used for data entry, and SPSS version 20 was used for the analysis. A bi-variable and multivariable logistic regression was used to determine factors associated with the attitude of health professionals towards tele-rehabilitation. Result: A total of 408 participants enrolled in the study, with a response rate of 95.5%. The majority 285(69.9%) of health professionals had good attitude towards tele rehabilitation-based treatment services. Good knowledge of tele rehabilitation [AOR = 1.76, 95%, CI: 1.078, 2.879], digitally literate [AOR = 1.74, 95%, CI: 1.028, 2.954], perception on security and privacy [AOR = 0.56, 95%, CI: 0.333, 0.944], and owns smart mobile phone [AOR = 1.9, 95%, CI: 1.007, 3.781] were significantly associated with attitude towards tele rehabilitation service. Conclusion: In this study the majority of the respondents had a good attitude towards tele rehabilitation services. Having own mobile, knowledge towards tele rehabilitation, digital literacy, perception on security and privacy to rehabilitation were found to be factors associated with attitude towards tele rehabilitation service. Therefore, the government and other responsible entities should consider enacting systems and strategies to encourage the use of mobile technologies for the management of disability, chronic diseases and for rural patients.